Ackee Growing in the Florida Home Landscape - Jonathan H. Crane; Carlos F. Balerdi (EDIS)
HS1128, an 8-page illustrated fact sheet by Jonathan H. Crane and Carlos F. Balerdi, provides information about this fruit which is a common ingredient in Jamaican cooking, but which is not recommended for home landscape use due to the fact that the fruit is extremely poisonous when it is under-developed or over-ripe. Includes references, cultural calendar, fertilizer recommendations and nutrient values. Published by the UF Department of Horticultural Sciences, January 2008.